Identification of fibrinogen as a plasma protein binding partner for lecanemab biosimilar IgG - Jean‐Pierre Bellier; Andrea M. Román Viera; Caitlyn Christiano; Juliana A. U. Anzai; Stephanie Moreno; Emily C. Campbell; Lucas Godwin; Amy Li; Alan Y. Chen; Sarah M. Alam; Adriana Saba; Han Bin Yoo; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Recombinant monoclonal therapeutic antibodies like lecanemab, which target amyloid beta in Alzheimer's disease, offer a promising approach for modifying the disease progression. Due to its relatively short half‐life, lecanemab administered as a bi‐monthly infusion (typically 10 mg/kg) has a relatively brief half‐life. Interaction with abundant plasma proteins binder in the bloodstream can affect pharmacokinetics of drugs, including their half‐life. In this study, we investigated potential plasma protein binding (PPB) interaction to lecanemab using lecanemab biosimilar. Methods Lecanemab biosimilar used in this study was based on publicly available sequences. ELISA and western blotting were used to assess lecanemab biosimilar immunoreactivity in the fractions of human plasma obtained through size exclusion chromatography. The binding of lecanemab biosimilar to candidate plasma binders was confirmed by western blotting, ELISA, and surface plasmon resonance analysis. Results Using a combination of equilibrium dialysis, ELISA, and western blotting in human plasma, we first describe the presence of likely PPB partners to lecanemab biosimilar and then identify fibrinogen as one of them. Utilizing surface plasmon resonance, we confirmed that lecanemab biosimilar does bind to fibrinogen, although with lower affinity than to monomeric amyloid beta. Interpretation In the context of lecanemab therapy, these results imply that fibrinogen levels could impact the levels of free antibodies in the bloodstream and that fibrinogen might serve as a reservoir for lecanemab. More broadly, these results indicate that PPB may be an important consideration when clinically utilizing therapeutic antibodies in neurodegenerative disease.